Differential gene expression analyses related to fruit yield of Jatropha curcas L. using RNA-seq. Issue 5 (3rd September 2018) - Hui, Wenkai; Yang, Yuantong; Wu, Guojiang; Wang, Yi; Zaky Zayed, Mohamed; Chen, Xiaoyang
Abstract: Jatropha curcas L. seeds possess high oil content. However, the low fruit yield is a bottleneck for its utilisation in biodiesel production. To date, the genes related to fruit yield of J. curcas are still poorly studied. Therefore, this study was conducted to compare the transcriptome profiles of two J. curcas clones with high and low fruit yield. The results showed that 52 381 unigenes were obtained and annotated to 55 orthologous terms. More than 9 653 single nucleotide polymorphisms (SNPs)/Indels and 15 971 SSR loci were identified. In addition, 76 differential expression genes (DEGs) were obtained and mainly down-regulated in a high fruit yield sample. Moreover, the DEGs were significantly enriched in phytohormone signalling pathways, including gibberellin, brassinolide and jasmonic acid. Furthermore, we suggested that some genes might inhibit the initiation of female floral differentiation to decrease the fruit yield in J. curcas. These data will create a reference transcriptome for the genomics database of J. curcas for future studies. We expect that the dataset will serve as a foundation to study the genes function, which help in engineering high-yielding varieties in J. curcas .